2016
DOI: 10.1111/jph.12545
|View full text |Cite
|
Sign up to set email alerts
|

Infection Process of Burkholderia glumae in Rice Spikelets

Abstract: Burkholderia glumae, which causes bacterial panicle blight of rice (BPBR), is a well‐known pathogen. The pathogen‐induced symptoms include seedling rot, grain rot and leaf‐sheath browning in rice plants. B. glumae can incubate in rice plants as endophytes before booting stage of rice. In this study, we constructed a gfp‐labelled system of B. glumae LMG 2196 and used SEM to clarify the colonization course of B. glumae at the heading stage. New locations of B. glumae were found. The pathogens initially distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Therefore, there are mainly two hypotheses of the entry of this pathogen to the plant. The first involves bacterial penetration through natural openings and/or wounds on roots, leaves and/or spikelet from an environmental reservoir of the bacteria ( Hikichi, 1993 ; Li et al, 2017 ; Tsushima et al, 1996 ). Direct spraying of B. glumae on plant leaves and spikelets has provided support for this mechanism of entry ( Tsushima et al, 1996 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there are mainly two hypotheses of the entry of this pathogen to the plant. The first involves bacterial penetration through natural openings and/or wounds on roots, leaves and/or spikelet from an environmental reservoir of the bacteria ( Hikichi, 1993 ; Li et al, 2017 ; Tsushima et al, 1996 ). Direct spraying of B. glumae on plant leaves and spikelets has provided support for this mechanism of entry ( Tsushima et al, 1996 ).…”
mentioning
confidence: 99%
“…Direct spraying of B. glumae on plant leaves and spikelets has provided support for this mechanism of entry ( Tsushima et al, 1996 ). More recently, Li and colleagues, sprayed directly a bacterial suspension of the B. glumae LMG 2196 strain, expressing the green fluorescent protein ( gfp ) gene, on leaves of plants at tillering stage using 10 ml at 1 × 10 9 cfu.ml −1 ( Li et al, 2016 ) and on spikelets using 1 ml at 7 × 10 8 cfu.ml −1 ( Li et al, 2017 ). These authors successfully showed B. glumae rice plant colonization of the vascular bundle through stomas, epidermal and leaf hairs infection ( Li et al, 2016 ), and colonization of gynoecium and stamens, after bacterial cell proliferation on glumae and penetration through glumae hairs ( Li et al, 2017 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are no reports describing the invasion process of the Cm through the outer epidermis openings to specific locations within the epidermis in tomato hosts. An analysis of Burkholderia glumae, which is another bacterial species that infects plant vascular tissues, revealed that epidermal hairs and leaf hairs are the initial colonization sites [19]. Researchers examining the interior of maize leaves infected with another Clavibacter species observed that, after passing through the outer epidermis, C. nebraskensis colonizes leaves through epidermal junctions, cuticle depressions, stomata and the surrounding area, and the trichome base [20].…”
Section: Initial Infection Of Plants By CMmentioning
confidence: 99%
“…Based on studies was conducted by Li et al (2016) with the gfp gene marker, initially, B. glumae was in rice plants before panicle formation. Pathogenic bacteria initially surround the glume surface and colonize until the population increases in the glume hairs.…”
Section: Rice Plantsmentioning
confidence: 99%